State-Owned Enterprises in Bosnia and Herzegovina : Assessing Performance and Oversight - Cegar, Bobana (IMF Working Papers; Working Paper ;, 2019)
Based on a new database of State-Owned Enterprise (SOE) financial statements, we find that SOEs in Bosnia and Herzegovina are mostly in poor financial shape. We estimate the overall size and composition of the SOE sector, and identify individual companies that affect fiscal and macroeconomic performance. Financial analysis suggests that SOEs are not contributing enough to the economy. We also review the SOE governance framework and find that governments do not exercise their ownership function in line with WB/OECD guidelines. Reforms to the governance frameworks are necessary to foster transparency and improve accountability. More fundamental reform of the SOE sector might increase overall GDP by 3 percent per year.